ANALISIS PENERAPAN MANAJEMEN RISIKO PEMBIAYAAN PADA LEMBAGA PEMBIAYAAN SYARIAH - Syathir Sofyan (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
This research discusses financing risk management in sharia financing institutions. Financing risk is a risky risk and can lead to systemic risk one of which occurred the global financial crisis. Sharia financing institutions are identical with those risks, so that the application of proactive risk management should be done so as not to be affected. The purpose of this research is to know the risk management of financing at PT XYZ, which in this research is qualitative decriptive. Data analysis used is data reduction, data presentation, verification andconclusion. The results of this study indicate that the implementation of risk management of financing at PT XYZ is categorized not good enough. this means that to create financing risk management it is necessary to apply a reliable and consistent risk management system. Seeing the results of the research that during the period 2014 to 2016 has increased the value of NPF, which requires companies to act quickly to mitigate the value of NPF ratio